Surgical management of radial head luxation in a dog using an external skeletal traction device - Fitzpatrick, N.; Yeadon, R.; Farrell, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A five-month-old Airedale Terrier was presented with a history of right thoracic limb lameness. Clinical and radiographic examinations revealed caudolateral luxation of the right radial head. Surgical intervention involved an oblique proximal radial osteotomy and gradual craniomedial traction of the radial head using an external skeletal fixator (ESF) incorporating a traction device. The radial head was gradually reduced over 16 days. After radiographic confirmation of appropriate radial head reduction, a consolidation phase followed, with removal of the traction ESF after 24 days. Follow-up radiographs documented remodelling of the radial head. Clinical follow-up three years postoperatively revealed nearly normal ground reaction forces. Activity was unrestricted and there was no requirement for analgesic medications.
Keywords: Radial head; luxation; congenital; elbow; incongruity